Measuring and relating self-efficacy in java programming among computer science undergraduates in the South-West, Nigeria - Dr. Josiah Owolabi (African Journal of Behavioural and Scale Development Research, 2019)
The role that self-efficacy plays in the choice, effort as well as perseverance of a learner makes it very important to measure the self-efficacy scores in JAVA programming (SESJP) of computer science undergraduates and also to investigate its relationship with some selected variables (background in general programming language (C++), number of programming courses taken and institution types). This study made use of survey design of a correlational type. Two hundred and fifty-four (254) computer science undergraduates from four universities in the South-West, Nigeria, were selected using purposive sampling. Data was collected using a Self-Efficacy in Java programming scale (SEJPS) that contains thirty-two (32) items. The instrument was validated using Cronbach alpha approach that yielded a coefficient of 0.96. Descriptive statistics, Correlation and regression were used for data analysis. The mean and standard deviation scores for SEJPS were found to be x(134.89) and SD (45.39) respectively. The mean of 134.89 out of the maximum obtainable score for the scale which is 224,translates to 60.22% and this is above average. The number of programming courses taken before JAVA programming class as well as their background in C++ were found to significantly predict self-efficacy in JAVA programming. It was therefore recommended that computer undergraduates be made to take more prerequisite courses (C++ inclusive) before exposure to JAVA programming.